2006
DOI: 10.1159/000093249
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Atopy Patch Test and Skin Prick Test by Pretreatment with 1% Pimecrolimus Cream

Abstract: Background: In a subgroup of patients with atopic eczema (AE), aeroallergens are relevant eliciting factors. The atopy patch test (APT) was proposed as inflammation model for AE. Objective: It was the aim of this study to investigate the effect of pretreatment with 1% pimecrolimus cream (Elidel®) on the APT and skin prick test (SPT). Methods: In a randomized, controlled, double-blind study, 20 patients with AE and positive SPT and APT screening reaction to house dust mite Dermatophagoides pteronyssi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…In summary, a satisfactory therapy of chronic inflammatory disease such as AE should reduce symptoms, prevent relapses/flares and provide long-term management with high safety also for children. [64][65][66][67]63,[68][69][70] 3. Introduction to the compound SDZ ASM 981, an ascomycin derivate, is a compound in a novel class of anti-inflammatory macrolactams developed more than 20 years ago --known today as pimecrolimus, a calcineurin inhibitor.…”
Section: Overview Of the Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, a satisfactory therapy of chronic inflammatory disease such as AE should reduce symptoms, prevent relapses/flares and provide long-term management with high safety also for children. [64][65][66][67]63,[68][69][70] 3. Introduction to the compound SDZ ASM 981, an ascomycin derivate, is a compound in a novel class of anti-inflammatory macrolactams developed more than 20 years ago --known today as pimecrolimus, a calcineurin inhibitor.…”
Section: Overview Of the Marketmentioning
confidence: 99%
“…After 3 years, Weissenbacher et al showed that pimecrolimus pretreatment has a potential to suppress the development of lesions induced by aeroallergens exposure in patients with AE [70]. Following these facts, Wollenberg et al suggested the proactive therapy of AE, 'an emerging concept', by using topical TCIs several times a week resulting in less disease exacerbation and better quality of life [71].…”
Section: Clinical Efficacymentioning
confidence: 99%
“…The development of a standardized APT for food allergy is a future plan, as well as a study on the mechanisms of APT reactions involving both patients with intrinsic and extrinsic AE and investigating the role of the Fc ε receptor I and allergen-specific T-cell populations. Furthermore, the APT will be used in trials on topical and systemic therapy for AE and is evaluated as itch model [70,71]. Other aeroallergens of regional significance are to be standardized.…”
Section: The Future Of the Aptmentioning
confidence: 99%
“…Having stated the central role of topical corticosteroids, we must also recognize the substantial benefits we gained from topical calcineurin inhibitors [140][141][142][143][144][145][146][147][148][149]. In the last few years, the medical community has gained much understanding on this group of medications regarding its desirable actions and potential side effects [140][141][142][143][144][145][146][147][148][149].…”
Section: Therapeutic Advancesmentioning
confidence: 99%
“…In the last few years, the medical community has gained much understanding on this group of medications regarding its desirable actions and potential side effects [140][141][142][143][144][145][146][147][148][149]. Specifically, these inhibitors improved skin inflammation in patients with atopic dermatitis, likely through the mechanisms of regulatory T cell correction [141], depletion of plasmacytoid dendritic cells [142], suppressing expressions of the cytokine IL-5, the chemokines eotaxin and RANTES, and the chemokine receptor CCR3 [145], induction of apoptosismediated T cell depletion [146], reduction of dermal infiltration of cytokineexpressing inflammatory cells [147,148], and suppression of skin response to aeroallergens [143], while at the same time they do not appear to hinder the immune system to respond to vaccination [140,149]. The recent 'black box' warning label placed by the FDA on these inhibitors casts a cloud for the longterm use of this group of medications.…”
Section: Therapeutic Advancesmentioning
confidence: 99%